Kinerja Pengomposan Lubang Resapan Biopori Ditinjau dari Lokasi, Musim dan Penambahan Bahan Aditif - Yenni Ruslinda; Suci Mahdianti; Resti Ayu Lestari; Hendra Gunawan (Jurnal Serambi Engineering, 2023)
AbstractBiopore Infiltration Hole (BIH) Composting is influenced by the compost raw material's type, composition, and size, the addition of additives and activators, soil texture, land use, and weather conditions. Composting performance can be improved if these factors can be optimized. This study aims to analyze the performance of BIH composting in terms of location, season, and additives. Composting is done by varying the location/season, type, and weight of additives. For locations/seasons, composting is carried out in protected areas representing the dry season and open areas representing the rainy season. Variations of additives consist of no additives, 100% sawdust, 100% rice husks, and a mixture of sawdust and rice husks with variations in the weight of additives of 1.5% and 3% of the weight of the compost raw material. The analysis was carried out on the maturity test, the quality of physical and macro elements, and the quantity of compost. The results showed that all variations of composting had met the quality standards of domestic organic waste compost according to SNI 19-7030-2004 to test the maturity and quality of compost. The addition of additives can speed up the composting time by 2-6 days and increase 7.15-35.71% the quantity of solid compost. Composting with the addition of 100% rice husk additives at 1.5% of the weight of the compost raw material and carried out in protected locations (dry season) is the most optimal BIH composting.Keywords: additives, composting, Biopori Infiltration Holes (BIH), location, season